IS SOUTH AFRICA APART? ASSESSMENT OF AN URBAN HYBRIDITY. - (:unkn) unknown (My University, 2016)
Is the South African urban system apart? What properties are shared with other systems of cities? How are transferred, in these cities, the processes that can be noted in other territorial contexts? These investigations are at the heart of this volume Scientific Position and Project. From a comparative approach with the United States and France, the aim is to provide both theoretical and methodological insights on the possible specificities of the South African case study. It means to decide what can be seen as common dynamics, shared by all cities in the world, and what is related to the specific territorial identity. Through an exploratory approach, focused, on one hand, on the settlement and urbanization processes, and on the other hand, on the socio-economic transformations of cities and their capacity to adapt to change, what is argued is that this urban system is hybrid, produced by multiple interferences, and by spatio-temporal cross-breeding of processes.
Keywords: African Research